Vitamin D attenuated 6-OHDA-induced behavioural deficits, dopamine dysmetabolism, oxidative stress, and neuro-inflammation in mice. (3rd April 2022) - Bayo-Olugbami, Adedamola; Nafiu, Abdulrazaq Bidemi; Amin, Abdulbasit; Ogundele, Olalekan Michael; Lee, Charles C.; Owoyele, Bamidele Victor
ABSTRACT: Background : L-DOPA, the predominant therapy for Parkinson's disease (PD) is associated with motor deficits after prolonged use. The nigrostriatal tract, a primary target of neurodegeneration in PD, contains abundant Vitamin-D receptors, suggesting a potential role for VD in the disease. Therefore, we tested the impact of Vitamin D3 (VD3) in a mouse model of PD. Methods : PD was induced in adult male C57BL6 mice by a single intrastriatal injection of 6-hydroxydopamine. Two weeks post lesion, these mice received injections of a vehicle, VD3, L-DOPA, or a combination of VD3/L-DOPA and compared with sham controls. Treatment lasted three weeks, during which motor-cognitive neurobehaviour was assessed. Five weeks post lesion, brains were collected and striatal levels of the following proteins assessed: tyrosine hydroxylase (TH), dopamine decarboxylase (DDC), monoamine oxidase (MAO-B), Catechol-O-methyl transferase (COMT), dopamine transporter (DAT), brain-derived neurotrophic factor (BDNF), microglia marker (CD11b), inflammation (IL-1β), apoptotic signaling (BAX) and oxidative stress (p47phox). Results : Treatment with VD3 attenuated behavioural deficits induced by 6-OHDA, protein associated with dopamine metabolism and biomarkers of oxidative stress. VD3 significantly increased contralateral wall touches, exploratory motor and cognitive activities. VD3 significantly enhanced the expression of TH, DAT, BDNF, while significantly reducing expression of MAO-B, CD11b, IL-I β and p47phox. Conclusion : VD3 reversed some of the 6-OHDA induced changes in proteins involved in modulating the dopamine system, behavioural deficits and oxidative stress biomarkers. The data suggests that VD3 might be beneficial in reducing L-DOPA dosage, thereby reducing problems associated with dosage and prolonged use of L-DOPA in PD management.